Phylogeny of Cas9 determines functional exchangeability of dual-RNA and Cas9 among orthologous type II CRISPR-Cas systems - Fonfara, Ines (Oxford University Press, 2014)
The CRISPR-Cas-derived RNA-guided Cas9 endonuclease is the key element of an emerging promising technology for genome engineering in a broad range of cells and organisms. The DNA-targeting mechanism of the type II CRISPR-Cas system involves maturation of tracrRNA:crRNA duplex (dual-RNA), which directs Cas9 to cleave invading DNA in a sequence-specific manner, dependent on the presence of a Protospacer Adjacent Motif (PAM) on the target. We show that evolution of dual-RNA and Cas9 in bacteria produced remarkable sequence diversity. We selected eight representatives of phylogenetically defined type II CRISPR-Cas groups to analyze possible coevolution of Cas9 and dual-RNA. We demonstrate that these two components are interchangeable only between closely related type II systems when the PAM sequence is adjusted to the investigated Cas9 protein. Comparison of the taxonomy of bacterial species that harbor type II CRISPR-Cas systems with the Cas9 phylogeny corroborates horizontal transfer of the CRISPR-Cas loci. The reported collection of dual-RNA:Cas9 with associated PAMs expands the possibilities for multiplex genome editing and could provide means to improve the specificity of the RNA-programmable Cas9 tool.